1968
DOI: 10.2466/pr0.1968.22.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Introductory Phrases and Tonal-Facial Suggestion upon Question-Elicited Responses

Abstract: 18 variously-biased phrasings of 2 questions were administered by 20 interviewers pretending to endorse the given phrasing to 1164 college students. Random telephone interviews and quota personal interviews indicated that substantial ‘changes' in ‘opinion’ (on the order of about 13%) could be effected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…One of his more relevant early studies was that which measured whether questionnaires can be affected by interviewers who pretend to endorse the questions they ask. He found that substantial changes in opinion could be effected in this manner (Cameron, 1968). Of his early work, most noteworthy was his research on the use of tobacco.…”
Section: A Body Of Accumulated Evidencementioning
confidence: 99%
“…One of his more relevant early studies was that which measured whether questionnaires can be affected by interviewers who pretend to endorse the questions they ask. He found that substantial changes in opinion could be effected in this manner (Cameron, 1968). Of his early work, most noteworthy was his research on the use of tobacco.…”
Section: A Body Of Accumulated Evidencementioning
confidence: 99%